Motivasi dalam Manajemen Sumber Daya Pendidik Atau Tenaga Kependidikan di SDN Karanganyar 01 - Rofiq Hidayat; Qusi Nabila Maulidia; Nadia Mahsa Kalila; Muh 'Ainul Yaqin (Universitas Palangka Raya, 2024)
This study aims to analyze the role of motivation in teacher resource management at SDN Karanganyar 01 and its impact on teacher performance. Using a qualitative approach with interviews and observations, it was found that factors such as job satisfaction, recognition, and opportunities for self-development influence teacher motivation. The application of motivation theories such as Maslow, Herzberg, and McClelland suggests that the provision of incentives, training, and fair performance evaluations can enhance teacher satisfaction and performance. This study concludes that effective motivation positively contributes to teacher performance and the quality of education.